2018
DOI: 10.3389/fmicb.2018.01715
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Tulathromycin Metaphylaxis on the Fecal Resistome and Microbiome of Commercial Feedlot Cattle Early in the Feeding Period

Abstract: The objective was to examine effects of treating commercial beef feedlot cattle with therapeutic doses of tulathromycin, a macrolide antimicrobial drug, on changes in the fecal resistome and microbiome using shotgun metagenomic sequencing. Two pens of cattle were used, with all cattle in one pen receiving metaphylaxis treatment (800 mg subcutaneous tulathromycin) at arrival to the feedlot, and all cattle in the other pen remaining unexposed to parenteral antibiotics throughout the study period. Fecal samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 52 publications
(57 reference statements)
7
62
0
Order By: Relevance
“…Analogous effects are amenable to the use of antibiotics for prophylactic purposes [76,77]. In this view, antimicrobial compounds were commonly administered with the drinking water or the feed ration, ensuring a prolonged exposition of the animals to the low dosage of antibiotics for a prolonged time.…”
Section: Domestic Animal Husbandry Influence On Amrmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous effects are amenable to the use of antibiotics for prophylactic purposes [76,77]. In this view, antimicrobial compounds were commonly administered with the drinking water or the feed ration, ensuring a prolonged exposition of the animals to the low dosage of antibiotics for a prolonged time.…”
Section: Domestic Animal Husbandry Influence On Amrmentioning
confidence: 99%
“…Prophylactic-oriented administration of antibiotics in cattle husbandries expect the oral administration mainly to prevent respiratory diseases and/or liver abscesses [77,78]. Moreover, wide-spectrum antibiotics are administered intramammary during the non-lactating period, to prevent/reduce the incidence of mastitis in lactating animals [72].…”
Section: Domestic Animal Husbandry Influence On Amrmentioning
confidence: 99%
“…Gautier-Bouchardon et al [60] analyzed MICs for MB from cattle in France over 30 years, finding substantial increases for some macrolides (tylosin, tilmicosin, tulathromycin) and not others (gamithromycin, tildipirosin. In North America, CON calves would usually get a metaphylactic injection of tulathromycin on arrival at the feedlot [61] and tulathromyin is also used to treat active cases of BRD. Exposure to tulathromycin has increased its MIC in MH and not PM [62], in agreement with the results of our study for MH, although increased MICs for tulathromycin could also be influenced by co-selection.…”
Section: Factors Affecting Micsmentioning
confidence: 99%
“…In addition, the diversity and abundance of total ARGs were higher in the rumen of beef cattle fed high concentrate than those fed high forage diet, with chloramphenicol and aminoglycoside resistance genes being predominant in forage-and concentrate-fed cattle, respectively [13]. A recent study also suggested that the dietary supplementation of tulathromycin, a macrolide antimicrobial drug used as metaphylaxis, signi cantly affected the temporal development of fecal microbiota and associated resistome in feedlot cattle [51]. To our knowledge, there is no study reporting how host genetic factors affect the active gut resistome in mammalian species.…”
Section: Discussionmentioning
confidence: 99%